THE EFFECT OF KITA, MAJU, AND BERSAMA COASTAL AREAS RECLAMATION IN JAKARTA BAY ON WAVE HEIGHT USING SIMULATING WAVE NEARSHORE (SWAN) MODEL - Ardiansyah, Iqbal
is run on 1st October – 31st December 2007 using Simulating WAve Nearshore (SWAN) model, 1/4 wind data obtained from Cross-Calibrated Multi-Platform (CCMP), 1/120 bathymetry data derived from General Bathymetry Chart of the Oceans (GEBCO), and 1/600 National Bathymetry (BATNAS) data derived from Indonesian Geospatial Information Agency (BATNAS BIG). Simulation is done in two scenarios: before and after reclamation. Typhoon Hagibis and Mitag effect on significant wave height is analyzed using cross-correlation, that correlates between wind speed magnitude in the study area and significant wave height in Jakarta Bay from November 19th - December 13th, 2007. The result shows that the Typhoon Hagibis and Mitag on peak phase (November 23rd, 2007) affects significant wave height in Jakarta Bay after 11-day travel time, which is December 4th, 2007. Reclamation can result in either a decrease or increase of significant wave height in Jakarta Bay. After the reclamation, the largest of decrease of significant wave height occurred in the north of Bersama Coastal Area with a decrease of about 0,005 cm (3,33%) and the largest increase occurred in the area between Maju Coastal Area and Pantai Indah Kapuk with an increase of about 14 cm (77,78%) on 4th December 2007.